Vitamin k, warfarin and prothrombin: an alternate pathway to improve cancer survival (Hematology Meeting Reports, 2009)
Billroth first proposed a theoretical relationship between hemostatic mechanisms and the development of cancer metastasis in 1878. A lack of experimental animal models to study cancer metastasis inhibited further studies on hemostasis and cancer until the late 1960s and early 1970s.1 Since that time, studies using mouse and rat models, have demonstrated a reduction of tumor metastasis and improved animal survival with systemic anticoagulation. However, the therapeutic benefits observed in these models cannot be attributed to a single, specific intervention in the coagulation system since a variety of anticoagulants, anti-platelet and fibrinolytic agents appeared to be effective.1